The interleukin‐33 receptor ST2 is important for the development of peripheral airway hyperresponsiveness and inflammation in a house dust mite mouse model of asthma. Issue 3 (March 2016) - Zoltowska, A. M.; Lei, Y.; Fuchs, B.; Rask, C.; Adner, M.; Nilsson, G. P.
Summary: Background: Several clinical and experimental studies have implicated IL‐33 and its receptor ST2 in the development of asthma. However, the effect of IL‐33/ST2 signalling on airway responses and inflammation in allergic asthma is not well established. Objective: To investigate the role of IL‐33/ST2 signalling in promoting allergen‐induced airway hyperresponsiveness (AHR), airway inflammation, antigen‐specific IgE production and mast cell activity in a mouse model of asthma. Methods: ST2‐deficient (ST2 −/− ) mice and control BALB/c mice were given house dust mite (HDM) extract over a 6‐week period. Forty‐eight hours after the final HDM administration, lung function and airway inflammation were evaluated. Airway responsiveness was determined in the central airways and peripheral lung. Cellular infiltration and mast cell protease mMCP‐1 levels were quantified in bronchoalveolar lavage fluid (BALF). Recruitment of inflammatory cells and inflammatory cytokine profiles were assessed in pulmonary tissue, and HDM‐specific IgE was measured in serum. Results: ST2 deficiency diminished HDM‐induced AHR in the peripheral lung, while AHR in the central airways was unaffected. Inflammatory responses to HDM were also reduced in ST2 −/− mice as reflected by the lower induction of HDM‐specific serum IgE, inhibition of HDM‐induced eosinophilia and reduced macrophage count in BALF, and a diminished influx of inflammatory cells and reduced goblet cell hyperplasia around the peripheral airways. Furthermore, the levels of the inflammatory cytokines IL‐1β, IL‐5, IL‐13, IL‐33, GM‐CSF, thymic stromal lymphopoietin and mast cell protease mMCP‐1 were reduced in HDM‐treated ST2 −/− mice compared with wild‐type controls. Conclusions: In addition to promoting Th2 inflammation, we now suggest a role for the IL‐33/ST2 pathway for the induction of peripheral inflammation and mucus production that causes AHR in the peripheral lung. This mechanism for inducing AHR at distal parts of the lung may be of specific importance as asthma is considered as a small airway disease.